1982
DOI: 10.1037/0021-843x.91.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Season of birth and schizophrenia: A response to the Lewis and Griffin critique.

Abstract: A number of writers have published data suggesting that schizophrenics are particularly likely to have been born in the winter months. Lewis and Griffin have argued that this "seasonally" effect may be an artifact resulting from (a) the use of inappropriate expected values in the calculation of chi-squares in previous studies; (b) the age-incidence effect-the tendency of risk to increase with time in disorders whose incidence increases with age; and (c) the ageprevalence effect-the fact that people born early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
30
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 6 publications
4
30
0
Order By: Relevance
“…For example, Sarbin & Mancuso (1980) surveyed the Journal of Abnormal and Social Pychology (later the Journal of Abnormal Pychology) for the years 1959 1978 and found that 374 papers, filling a total of 2472 pages o r 15.3 per cent of the journal space, employed the presence o r absence of schizophrenia as an independent variable. Hypotheses that have been proposed to account for schizophrenic breakdowns have implicated nearly every variable known t o affect human behaviour, including brain biochemistry (Green & Costain, 1981), genetic endowment (Gottesman & Shields, 1982), neurological factors (Pincus & Tucker, 1978), diet (Singh & Kay, 1976); season of birth (Watson, Kacula, Anguluski & Bruun, 1982), hypothesized viral agents (Crow, 1984), social stress (Faris & Dunham, 1939), life-events (Brown & Birley, 1968) and family structure (Bateson, Jackson, Haley & Weakland, 1956).…”
mentioning
confidence: 99%
“…For example, Sarbin & Mancuso (1980) surveyed the Journal of Abnormal and Social Pychology (later the Journal of Abnormal Pychology) for the years 1959 1978 and found that 374 papers, filling a total of 2472 pages o r 15.3 per cent of the journal space, employed the presence o r absence of schizophrenia as an independent variable. Hypotheses that have been proposed to account for schizophrenic breakdowns have implicated nearly every variable known t o affect human behaviour, including brain biochemistry (Green & Costain, 1981), genetic endowment (Gottesman & Shields, 1982), neurological factors (Pincus & Tucker, 1978), diet (Singh & Kay, 1976); season of birth (Watson, Kacula, Anguluski & Bruun, 1982), hypothesized viral agents (Crow, 1984), social stress (Faris & Dunham, 1939), life-events (Brown & Birley, 1968) and family structure (Bateson, Jackson, Haley & Weakland, 1956).…”
mentioning
confidence: 99%
“…We (Watson, Kucala, Angulski, & Brunn, 1982) attempted to control the ageprevalence effect (and, to some degree, the age incidence effect) in a paper on schizophrenic birth seasonality by studying the birth months of schizophrenics using both January-December and July-June calendar years. We found highly significant winter birth excesses in these patients both before and after instituting that control.…”
mentioning
confidence: 99%
“…Many studies, especially in countries of the northern hemisphere, have reported that more schizophrenics are born during winter and early spring than during other seasons (1)(2)(3)(4)(5)(6)(7)(8). These investigations suggests that some environmental influence acting in utero or in the early months of life, and varying with the season of year, contributes to the etiology of at least some forms of schizophrenia (such as viral infection, obstetric or perinatal complications, malnutrition, vitamin deficiency or temperature) (9,10).…”
mentioning
confidence: 99%